PENGARUH DEWAN KOMISARIS INDEPENDEN, LIKUIDITAS, DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS - Vascha, Dio Torik; Rahayu, Sri; Sundjoto, Sundjoto (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
economic misery are finished earlier than a real financial ruin happens in a business enterprise. financial misery commonly happens because of fraud in management, not able to pay the employer's liabilies or money owed with property owned, and the earnings derived by using the company isn't always proportional to the entire belongings issued. The purpose of this examine is to decide the effect of unbiased board of commissioners, liquidity, profitability, and working potential to financial distress. The populace in this take a look at is a shipping company indexed at the Indonesia inventory alternate length 2020-2022. This sampling method the use of purposive sampling. statistics evaluation turned into processed the usage of SPSS model 24 software. The outcomes showed that the liquidity, profitability, and running potential variables influenced the economic distress, at the same time as the impartial board variable did now not affect the economic misery. key phrases : financial distress, independent board of commissioners, liquidity, profitability.